Determinan Keberlangsungan UMKM di Era New Normal - Kemal Farouq Mauladi; Purnomo Hadi Susilo; Ratna Eka Sari (Esensi: Jurnal Bisnis dan Manajemen, 2021)
The Covid-19 pandemic has created problems for SMEs. This study examines several factors that affect the sustainability of MSMEs during the Covid-19 pandemic. This study uses quantitative methods. Data collection techniques using questionnaires and literature study. The population of this study amounted to 130,000 MSME actors. The sample that became the respondent of this study was 200 MSME actors. The series of data tests that have been carried out have found several things, that product quality and the external environment have no effect on the sustainability of MSME businesses during the COVID-19 pandemic. Meanwhile, the use of e-commerce, capital readiness, and relaxation of taxes and banking credits have an effect on the sustainability of MSME businesses during the COVID-19 pandemic. The novelty of this research, namely testing of new variables that only exist in Indonesia, namely the relaxation of taxes and credits that emerged during the COVID-19 pandemic is intended for MSME actors to maintain business continuity.Cara Mengutip:Mauladi, K. F., Susilo, P. H., & Sari, R. E.. (2021). Determinan Keberlangsungan UMKM di Era New Normal. Esensi: Jurnal Bisnis dan Manajemen, 11(1), xx-xx. https://doi.org/10.15408/ess.v11i1.22038.